Recent advances in the diagnosis and treatment of DIHS/DRESS in 2025 - Yoshiko Mizukawa; Tetsuo Shiohara (Allergology International)
Drug-induced hypersensitivity syndrome (DIHS) or drug reaction with eosinophilia and systemic symptoms (DRESS) is a severe drug reaction characterized by a range of clinical manifestations. These range from mild cases resolving upon cessation of the causative drug to severe cases involving complex disease progression and potential fatality. A hallmark of DIHS/DRESS is the sequential reactivation of herpesviruses, particularly human herpesvirus 6 (HHV-6), during the disease course, contributing to recurrent symptoms. Viral reactivation can lead to critical complications, including infectious DIHS/DRESS-associated complications (iDACs) and autoimmune sequelae (aDACs). Managing DIHS/DRESS remains challenging due to its complexity, requiring precise prediction and tailored treatment strategies. Recent studies suggest that early-stage classification using the DIHS/DRESS Severity (DDS) score may help identify refractory cases, including DACs. Furthermore, early intervention with anti-cytomegalovirus (anti-CMV) therapy can mitigate iDACs caused by CMV reactivation, preventing progression to severe CMV-related diseases. Long-term follow-up is crucial, as aDACs can manifest even 3 years postonset. Serial monitoring is recommended, particularly in patients treated with intravenous immunoglobulin or corticosteroid pulse therapy, which are recognized risk factors for aDAC development. This review highlights DIHS/DRESS management strategies, focusing on its clinical features, the role of viral reactivation, and therapeutic interventions.